Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1007/s002619900033
|View full text |Cite
|
Sign up to set email alerts
|

Intussuscepted colonic lipomas: loss of fat attenuation on CT with pathologic correlation in 10 cases

Abstract: Lipomas may have an atypical appearance when intussuscepted due to varying degrees of infarction/fat necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 9 publications
(22 reference statements)
0
24
0
5
Order By: Relevance
“…On CT, lipomas appear ovoid or pear shaped, with sharp margins and with absorption densities of -40 to -120 houns field units, typical of fatty composition (13)(14)(15). Not all intussuscepted lipomas are characterized by homogeneous low attenuation on CT, and a study by Buetow and colleagues (16) showed that they might be mistaken for other neoplastic causes of intussusception such as adenocarcinoma, lymphoma, and metastasis. The changes in CT attention were directly related to the degree of infarction and fat necrosis seen within the lipoma, but the size and location of the intussuscepted lipoma were otherwise unrelated to CT findings.…”
Section: Discussionmentioning
confidence: 97%
“…On CT, lipomas appear ovoid or pear shaped, with sharp margins and with absorption densities of -40 to -120 houns field units, typical of fatty composition (13)(14)(15). Not all intussuscepted lipomas are characterized by homogeneous low attenuation on CT, and a study by Buetow and colleagues (16) showed that they might be mistaken for other neoplastic causes of intussusception such as adenocarcinoma, lymphoma, and metastasis. The changes in CT attention were directly related to the degree of infarction and fat necrosis seen within the lipoma, but the size and location of the intussuscepted lipoma were otherwise unrelated to CT findings.…”
Section: Discussionmentioning
confidence: 97%
“…En général, ils sont de petite taille et asymptomatiques [1]. Cependant, une minorité parmi eux peut être symptomatique et la fré-quence des symptômes est directement corrélée à la taille du lipome quand il est supérieur à 2 cm [3][4]. Nous venons d'en rapporter deux cas symptomatiques de localisation transverse et angulaire gauche.…”
Section: Discussionunclassified
“…Néanmoins, des images scannographiques atypiques liées à une composante nécro-tique du lipome, favorisée par l'invagination de ce dernier, ont été rapportées. Il peut alors être difficile de le différen-cier d'une tumeur maligne [3]. Pour nos patients, la TDM était suggestive du diagnostic et elle a permis de mettre en évidence l'invagination colocolique pour le deuxième cas.…”
Section: Discussionunclassified
“…Considering the age and symptoms of these patients, malignant tumors are also a matter of concern [11] . For the diagnosis, colonoscopy allows direct visualization of the submucosal lipoma, which appears as a mass covered by normal mucosa, but it can also show ulcerated or necrotic overlying mucosa [6,12,13] .Colonoscopic biopsy confirms the nature, but inadequate tissue samples often indicate nonspecific colitis with mucosal inflammation…”
Section: Discussionmentioning
confidence: 99%